2014
DOI: 10.1111/jtxs.12095
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Commercial Cheese Regarding Thermophysical Properties and Application of Multivariate Statistical Analysis to Elaborate Product Mapping

Abstract: A variety of 25 commercial cheese were analyzed by means of four different methods to evaluate thermophysical parameters in order to estimate methods with high potential to differentiate between cheese varieties. Rheological properties of different temperatures were obtained by a dynamic oscillatory shear test. Furthermore, stretchability, meltability and the formation of free oil were obtained. Principal component analysis was applied to the data set to receive a mapping of the cheese. A reduction of the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Similar results have been found by Solhi et al (2020), who reported tan δ values greater than one in processed cheeses at temperatures between 57.5-59.7 °C, and by Pastorino et al (2002), who attributed these changes to the modifications suffered by the cheese structure with the increase of temperature, causing changes in the scope and nature of the protein interactions. Other works where similar behaviors are reported includes the American processed cheese (Lu et al, 2002), Gouda type cheese (Schenkel et al, 2013), Gruyere, Raclette, Edam, Brie and Mozzarella cheeses (Schenkel et al, 2014), Cheddar cheese (Brickley et al, 2007), processed cheese (Hosseini-Parvar et al, 2015) and Mexican Manchego cheese (Lobato-Calleros et al, 2003).…”
Section: Rheological Characterizationsupporting
confidence: 53%
“…Similar results have been found by Solhi et al (2020), who reported tan δ values greater than one in processed cheeses at temperatures between 57.5-59.7 °C, and by Pastorino et al (2002), who attributed these changes to the modifications suffered by the cheese structure with the increase of temperature, causing changes in the scope and nature of the protein interactions. Other works where similar behaviors are reported includes the American processed cheese (Lu et al, 2002), Gouda type cheese (Schenkel et al, 2013), Gruyere, Raclette, Edam, Brie and Mozzarella cheeses (Schenkel et al, 2014), Cheddar cheese (Brickley et al, 2007), processed cheese (Hosseini-Parvar et al, 2015) and Mexican Manchego cheese (Lobato-Calleros et al, 2003).…”
Section: Rheological Characterizationsupporting
confidence: 53%
“…The flowability was conducted via Schreiber test according to Schenkel et al (2014). A cheese disc with defined diameter and height was heated for 8 min at 232°C.…”
Section: Flowabilitymentioning
confidence: 99%
“…Dynamic oscillatory shear measurements were conducted on a rheometer (Physica MCR 301, Anton Paar, Ostfildern, Germany) via temperature sweep experiments according to Schenkel et al (2014). Temperature increased during the measurement from 20 to 80°C at 3°C.min −1 at a constant deformation strain of 0.002 and a constant frequency of 1 Hz.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…However, the values for European Emmental cheese were fairly low, indicating a firmer structure and reduced meltability. Schenkel et al (2014) analysed 24 different commercial cheese types (one Emmental cheese sample and four Swiss-type cheese samples) and obtained tan δ max values from 2.46 to 3.46 for Swiss-type cheeses (Emmental cheese=3.12). Differences can be explained by variations in the manufacturing process such as scalding temperature, curd washing and brining duration.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation